Upaya Membangun Hubungan Yang Harmonis Antara Guru dan Orang Tua Siswa dalam Meningkatkan Kualitas Pembelajaran di Sekolah - Delila Maya Sari Siregar; Nabila Amanda Pulungan; Shelly Elprida Gajahmanik; Sri Yunita (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research discusses efforts to build harmonious relationships between teachers and parents in improving the quality of learning in schools. This research uses a library study research method using books, journals and other relevant sources as research guides. The research results show harmonious relationships between teachers and parents are able to improve the quality of learning in schools by creating a conducive learning environment and increasing student motivation and involvement. Apart from that, there are still several challenges that hinder the establishment of harmonious relationships between teachers and parents in improving the quality of education in schools.